SARS-CoV-2 infection in high-risk children following tixagevimab–cilgavimab (Evusheld) pre-exposure prophylaxis: a single-center observational study - Hijano, Diego R.; Ferrolino, Jose A.; Swift, Elizabeth G.; Michaels, Carolyn A.; Max, Anita; Hayden, Randall T.; Wolf, Joshua; Dallas, Ronald H.; Greene, William L.; Richardson, Julie L.; Hakim, Hana; Morton, Ted H.; et al. (Frontiers in Oncology, 2023)
From December 8th, 2021, to January 26th, 2023, tixagevimab-cilgavimab (T-C) was authorized for pre-exposure prophylaxis of COVID-19. During this period, we used a multidisciplinary team to communicate, screen, approach, and administer T-C to eligible patients. Twenty-seven patients were eligible. Of these, 24 (88.9%) received at least one dose of T-C, and three patients received two doses. Majority of patients were White, non-Hispanic, and females. Only two patients had COVID-19 prior to receiving T-C. Seventeen (70.8%) had received two or more doses of SARS-CoV-2 vaccine. No serious adverse events were noted. Seven patients developed SARS-CoV-2 infection within 180 days of receiving T-C (median 102 days; range 28-135), and only one patient developed severe COVID-19 requiring intensive mechanical ventilation in the intensive care unit. No patient died of COVID-19.